2009
DOI: 10.2527/jas.2009-2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein and bacterial lipopolysaccharide infusion on nitrogen metabolism and hormonal responses of growing beef steers1

Abstract: Purified lipopolysaccharide (LPS) infusion in cattle induces clinical and metabolic responses similar to gram-negative bacterial infection. Effects of LPS and dietary protein on rectal temperature, serum hormones, haptoglobin, plasma urea N and AA, and N balance were evaluated in 24 steers (250 +/- 2.8 kg of BW). Treatments were a 2 x 3 factorial of LPS (0 vs. 1.5 microg/kg of BW; -LPS vs. +LPS) and diets containing (DM basis) 1) 14.5% CP, 11.6% ruminally degradable protein (RDP), and 2.9% ruminally undegradab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 35 publications
9
49
3
Order By: Relevance
“…This increase in rectal temperature indicated that the LPS elicited a stress response. Similar increases in rectal temperature have been observed in response to LPS challenge in adult cattle (Waldron et al, 2003) and growing heifers 250kg weight (Waggoner et al, 2009a).…”
Section: Resultssupporting
confidence: 73%
“…This increase in rectal temperature indicated that the LPS elicited a stress response. Similar increases in rectal temperature have been observed in response to LPS challenge in adult cattle (Waldron et al, 2003) and growing heifers 250kg weight (Waggoner et al, 2009a).…”
Section: Resultssupporting
confidence: 73%
“…Dibner and Knight (2008) stated that oxidative stress in the gastrointestinal system is associated with loss of barrier function. Failure of the intestinal barrier can increase bacteria translocation (Walker and Sanderson, 1992) and subsequently increase protein degradation (Waggoner et al, 2009) and reduce feed intake (Elsasser et al, 1995;Steiger et al, 1999). Figure 1 shows the relation of calculated initial PV (the percentage of lipid source included in the dietary treatment times the initial PV of the source) and ADG.…”
Section: Methodsmentioning
confidence: 98%
“…Generally, the inflammatory response is a hallmark of immune stress. Previous studies have reported that the proinflammatory cytokines (IL-1, IL-6, TNF-a) can reduce the utilisation rate of nutrients (Feingold et al 2008;Waggoner et al 2009), and inhibit the growth performance (Sijben et al 2001). In this study, LPS injection significantly increased the contents of serum IL-1, IL-2 and IL-6, meanwhile, diet supplemented with AOE significantly reduced the serum content of IL-2 (on d 21) and IL-6 (on d 28); there was an interaction on IL-1 in broilers between LPS and AOE.…”
Section: Growth Performancementioning
confidence: 99%